P271 How can we improve paediatric simulation training in a mixed ED?. (June 2019) - Connellan, Claire; Dann, Lisa; Jones, Jennifer; Tormey, Peter; Ryan, Ethel
Abstract : Introduction: The high-risk, low-volume nature of paediatric emergencies can results in a lack of physician comfort and confidence in dealing with sick children. 1 Simulation training can help improve caregiver confidence and team communication and performance in paediatric emergencies. 1 Aims: Weekly, multi-disciplinary simulation sessions are held in the ED in UCHG. We sought to identify the baseline experience and confidence levels of those attending and to identify areas whereby the sessions could be improved. We then re-surveyed participants after 15 simulation sessions to identify how useful they found the sessions and to identify means of further improvement. Methods: Surveys were distributed to staff attending the weekly simulation sessions before and after 15 simulations sessions. Results: 17 baseline and follow up surveys were returned. The initial comfort level of respondents participating in simulations were: very uncomfortable (4), slightly uncomfortable (4), neither comfortable nor uncomfortable (6), comfortable (3), very comfortable (0). 10/17 respondents felt they learned more by participating in simulations and 7/17 felt that they learn more by observing. 15/17 found the scenarios 'helpful' or 'very helpful'. Suggestions to improve the sessions included: more consultant involvement (5), a registrar leading the scenario (4), longer, more complicated scenarios (6), involvement of more participants (8)and receiving the topic and study materials earlier in the week (7). We sought to implement these recommendations and then performed the follow up survey. After 15 simulation sessions 8/17 participants found the sessions very helpful and 9/17 found them helpful. 6/17 'strongly agreed' and 10/17 'agreed' that the sessions improved their confidence in participating in simulations. 10/17 participants felt they learned more by observing the simulations. 17/17 participants found the sessions helpful and 15/17 felt they improved their confidence dealing with sick children. Feedback on improvements made to the sessions was variable and suggestions for further improvement were received. Conclusions: 100% of participants felt the sessions were helpful and 88% felt they improved their confidence dealing with sick children. Low-fidelity, in-situ simulation can improve caregiver confidence but it important to be aware of the various levels of experience within your department and to seek feedback and strive for constant improvement. References: Cristallo, T., Walters, M., Scanlan, J., Doten, I., Demeter, T., & Colvin, D. (2018). Multidisciplinary, In Situ Simulation Improves Experienced Caregiver Confidence With High-Risk Pediatric Emergencies. Pediatric Emergency Care, 1.